KEARIFAN LOKAL HUYULA MASYARAKAT GORONTALO SEBAGAI MEDIA PENDIDIKAN ANTI KORUPSI - Supandi Rahman (Tadbir: Jurnal Manajemen Pendidikan Islam, 2022)
Prevention of corruption through strengthening local wisdom has not been done much. Departing from this, the purpose of this study is to reveal efforts to develop an anti-corruption education culture in the community through the implementation of the Huyula culture of the Gorontalo community. This research uses a qualitative approach with a literature study method. The results of the study indicate that the implementation of Huyula can be a community effort in cultivating anti-corruption values. The typical behavior of the Gorontalo people, which is starting to be difficult to find, is considered to be a medium for educating anti-corruption values, including honesty, discipline, responsibility, hard work, simple, independent, fair, brave, and caring. The suggestions that the author can give through this research are: 1) Indonesia is a storehouse of local wisdom which of course contains positive values, including the huyula tradition of the Gorontalo community, so it must be preserved; 2) cultivating anti-corruption values ​​through the implementation of the huyula tradition which is included in non-formal education is expected to be a reference in learning in formal education in schools and universities so that it has sustainable benefits.